Gentle is better: The original “gentle technique” for fat placement in breast lipofilling - Pietro Gentile (Journal of Cutaneous and Aesthetic Surgery, 2018)
Context: Breast lipofilling usually involves three different stages (harvesting, processing, and placement), and in each of these phases, adipocyte cells can be damaged. Our technique of fat placement is quite different from the others as we focus our attention on the last stage of fat graft procedure, which could explain the better results in graft survival. Aims: Our method is focused on eliminating any unnecessary manipulation of the graft so as to optimize graft retention and clinical outcomes: Controlled movement and slow rate of fat injection are the cornerstone of our technique and guarantee a nontraumatic fat transfer and a greater survival rate of adipocytes. Settings and Design: This was a retrospective cohort study. Materials and Methods: Of 120 patients (average age 41,5 years) affected by breast soft tissue defects, 60 were managed with the lipofilling procedure using fat graft injected by “Gentle technique.” To establish the effects of the injection’s procedure, we compared the results obtained in fat graft maintenance with a control group made up of 60 patients, treated with fat graft injection according to Coleman procedure. Statistical Analysis Used: Values are expressed as mean plus standard error and analyzed using Student’s t test. Results: In patients treated with Gentle technique, we observed a 60.5% + 12.5% maintenance of contour restoring and three-dimensional volume after 1 year (P < 0.0001 vs. control group); we compared the results obtained with only 39% + 4.4% of the control group treated with fat graft injected according to Coleman. Conclusions: Controlled 26 movement and slow rate of fat injection are the cornerstone of our technique and guarantee a nontraumatic fat transfer and a greater 27 survival rate of adipocytes.